Viruses infecting marine molluscs - Arzul, Isabelle; Corbeil, Serge; Morga, Benjamin; Renault, Tristan (Journal of Invertebrate Pathology, 2017)
Although a wide range of viruses have been reported in marine molluscs, most of these reports rely on ultrastructural examination and few of these viruses have been fully characterized. The lack of marine mollusc cell lines restricts virus isolation capacities and subsequent characterization works. Our current knowledge is mostly restricted to viruses affecting farmed species such as oysters Crassostrea gigas, abalone Haliotis diversicolor supertexta or the scallop Chlamys farreri. Molecular approaches which are needed to identify virus affiliation have been carried out for a small number of viruses, most of them belonging to the Herpesviridae and birnaviridae families. These last years, the use of New Generation Sequencing approach has allowed increasing the number of sequenced viral genomes and has improved our capacity to investigate the diversity of viruses infecting marine molluscs. This new information has in turn allowed designing more efficient diagnostic tools. Moreover, the development of experimental infection protocols has answered some questions regarding the pathogenesis of these viruses and their interactions with their hosts. Control and management of viral diseases in molluscs mostly involve active surveillance, implementation of effective bio security measures and development of breeding programs. However factors triggering pathogen development and the life cycle and status of the viruses outside their mollusc hosts still need further investigations.